2021
DOI: 10.48129/kjs.v48i2.9006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Injana claystone from Central Iraq for the brick industry

Abstract: This study aims to suggest an alternative to the use of quality agricultural soil in the brick industry (Iraq). The Late Miocene claystone bed in the Injana Formation in central Iraq was targeted through the study of 18 exposed sections that were sampled by using the trench sampling method. The claystones are characterized by quartz (36.4%) followed by calcite (32.8%), quartz (36.4%) feldspar (2.6%), gypsum (1.3%) and dolomite (0.7%), kaolinite (10.5%), illite (7.7%), chlorite (6.7%), palygorskite (6.0%) and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The investigation stage of the clays for a specific quarry is depending on the values of silica, alumina, iron oxides, calcium carbonate, and magnesium, as well as sulfates, which are determined by the so-called laboratory specification, to match the existing oxides in the limestone, which enter a main potential within the raw materials (Reyes et al, 2017). Awad and Awadh )2020) and Awadh, and Awad (2021) have determined the evaluation of the clay from the ancient layers for the manufacture of the cement and bricks (ordinary and perforated) as an additional source for Cement industry. Shaker, )2019) studied the physical, chemical, and mineralogical properties in this area and investigated the air pollution of the contaminated gas and dust of the Private brick factories.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation stage of the clays for a specific quarry is depending on the values of silica, alumina, iron oxides, calcium carbonate, and magnesium, as well as sulfates, which are determined by the so-called laboratory specification, to match the existing oxides in the limestone, which enter a main potential within the raw materials (Reyes et al, 2017). Awad and Awadh )2020) and Awadh, and Awad (2021) have determined the evaluation of the clay from the ancient layers for the manufacture of the cement and bricks (ordinary and perforated) as an additional source for Cement industry. Shaker, )2019) studied the physical, chemical, and mineralogical properties in this area and investigated the air pollution of the contaminated gas and dust of the Private brick factories.…”
Section: Introductionmentioning
confidence: 99%
“…Awad and Awadh (2020) studied reserve estimation of Late Miocene Injana claystone beds for portland cement and brick industry in Iraq determined as a proven reserve by using triangle and GIS method. and Awadh and Awad (2021) manufactured perforated and ordinary bricks using injana claystone in Karbala-Najaf plateau in the middle of Iraq, the researchers concluded that Injana claystone is suitable for such purposes. Najim and Yousif (2021) studied the Synthesis of Industrial Ceramic (Cordierite) from Iraqi Raw Materials Through Solid-State Sintering Method in Western Dessert used XRD for measuring the best mixture for preparing cordierite ceramics.…”
Section: Introductionmentioning
confidence: 99%